Changing Current Net Nutrition with Weight as a Measure of Net Nutritional Change with the Transition from Bound to Free Labor: A Difference-in-Decompositions Approach - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2019)
A population's weight conditioned on height reflects its current net nutrition and demonstrates health variation during economic development. This study builds on the use of weight as a measure for current net nutrition and uses a difference-in-decompositions technique to illustrate how black and white current net nutrition varied with the transition to free-labor. Adult black age-related weight gain was greater with the transition to free-labor yet was not as large as the adult white age related weight gain. Agricultural worker's current net nutrition was better than workers in other occupations, and agricultural workers' net nutrition was better than workers in other occupations but was worse-off with the transition to free labor. Nativity had the greatest effect with weight changes and the transition to free-labor. Within-group weight variation was greater than across-group variation.
Keywords: C10; C40; D10; I10; N30; 330; weight variation; current net nutrition; Oaxaca decomposition